PERKEMBANGAN BERMAIN DALAM PERMAINAN TRADISIONAL (CONGKLAK) UNTUK MELATIH MOTORIK KASAR, SOSIAL DAN EMOSIONAL PADA ANAK USIA DINI - Indar Rahman, Khofifah; Khadijah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
Playing is every child's desire. Play is also defined as a place for children to express all forms of behavior that are fun and without coercion. "According to the KBBI, a game is something that is used for playing, either in the form of goods or something that can be used for playing." There are many types of gaming tools that have developed over time. Starting from traditional to modern games. Types of games that form skills and creativity, such as the congklak game. This game requires control from parents or teachers so that the type and equipment of the game can function optimally and not harm children. The aim of this research is so that children can get to know traditional games from an early age, and can train children's gross motor skills, social emotions, and can practice cooperation with other friends. The research method uses a library research or library research approach. namely studies carried out in libraries and also in the environment by reading, studying, or browsing library materials. As well as taking data from journals and books that can support this research.